Air Pollution Exposure as a Relevant Risk Factor for Chronic Obstructive Pulmonary Disease Exacerbations in Male and Female Patients - Miguel Enrique Silva Rodriguez; Patricia Silveyra (European Medical Journal)
Chronic obstructive pulmonary disease (COPD) is a multifactorial lung inflammatory disease that affects 174 million people worldwide, with a recently reported increased incidence in female patients. Patients with COPD are especially vulnerable to the detrimental effects of environmental exposures, especially from air particulate and gaseous pollutants; exposure to air pollution severely influences COPD outcomes, resulting in acute exacerbations, hospitalisations, and death. Here, a literature review of the recent work addressing air pollution-induced acute exacerbations of COPD (AECOPD) was conducted in order to determine whether sex was considered as a biological variable in these studies, and whether air pollution exposure affected patients with COPD in a sex-specific manner. It was found that, while the majority of studies enrolled both male and female patients, only a few reported results were disaggregated by sex. Most studies had a higher enrolment of male patients, only four compared AECOPD outcomes between sexes, and only one study identified sex differences in AECOPD, with females displaying higher rates. Overall, this analysis of the literature confirmed that air pollution exposure is a trigger for AECOPD hospitalisations and revealed a significant gap in the knowledge of sex-specific effects of air pollutants on COPD outcomes, highlighting the need for more studies to consider sex as a biological variable.